IMPLEMENTATION OF BINNENDIFFERENZIERUNG IN WRITING FOR GERMAN LEARNERS AS DAF - Julaikah, Dwi Imroatu; Mustofa, Ali; Titaley, Audrey; Rusmiyati; Ridwan, Agus; Bingku, Soflies Marry E. (Universitas Negeri Surabaya, 2025)
German is widely taught as a foreign language (DaF; Deutsch als Fremdsprache) in Indonesia. However, observations during German language instruction at Universitas Negeri Surabaya (UNESA) have revealed that writing skills pose a significant challenge for many learners. Preliminary observations suggest that diverse language proficiency levels is a primary contributing factor to this challenge. Notably, a substantial portion of German Education students at UNESA did not have prior German language course’s exposure in high school. In light of these observations, the present study underscores the urgency of implementing Binnendifferenzierung, a differentiated instruction approach, to address the diverse skill levels among learners. This qualitative descriptive research aims to describe the implementation of Binnendifferenzierung—differentiation learning—in the